A nomeação na Bahia setecentista: estudo da toponímia de base portuguesa no Mapa da Capitania da Bahia de Todos os Santos (1761-1807) - Santiago, Iago Gusmão (2021)
The present dissertation is a toponymic study in which 212 Portuguese-based toponyms registered on a map of the Capitania da Bahia de Todos os Santos were analyzed. The corpuswas extracted from three documents that are available in the digital collection of the Biblioteca Nacional and their dating was attributed between the period from 1761 to 1807 (HAVRE, 2019). The study of this corpus is justified by the fact that the maps present orality marks in the spelling of the toponyms and because they register an expressive number of microtoponyms from the inland areas of Bahia, which does not occur in cartographic works of the period. The preparation of the data for the analysis was carried out by means of rasterization and the transcription of the toponyms with the indication of the location on the maps. For the analysis of the toponyms, a lexicographic-toponymic form was created, idealized to describe the names in the etymological, graphic and phonetic, morphosyntactic and semantic levels. In this study, it is also presented a proposal to classify the naming mechanisms focused on the Brazilian reality. This research is based on the theoretical methodological principles of lexicology (BIDERMAN, 2001; LARA, 2005), of descriptive toponomastics, with regard to discussions on toponymic dynamics (TRAPERO, 1995; SEABRA, 2004, 2006b; BARREIROS e BARREIROS, 2016; among others), the classification of semantic motivation (DORION and HAMELIN, 1966; DICK, 1980; 1990; 1992; AGUILERA, 1999, among others), and the classification of naming mechanisms (STEWART, 1954; 1970; 1975; TENT and BLAIR, 2011). The three maps have 411 occurrences, corresponding to 359 toponyms, of which only 212 are Portuguese-based, and the others are hybrids or from other strata. From the Portuguese toponyms, 50 are accidents of physical nature and 162 of human nature, in which processes of change were identified at the phonetic and morphosyntactic level, in addition to the presence of innovative dialect units. As for taxonomies, those of anthropo-cultural nature predominate, with 128 occurrences, while those of physical nature total 84 occurrences. Regarding the mechanisms, were identified 86 processes of toponymization, 104 of description and 22 hybrids. This dissertation also has a toponymicum corpus listed in the appendix A. Finally, the descriptive contribution of the Bahian toponymy of the colonial period and the theoretical-methodological contribution, based on the proposed analysis of the naming mechanisms, stand out in this work.